2007
DOI: 10.1136/qshc.2006.019042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crew resource management on diabetes care and patient outcomes in an inner-city primary care clinic

Abstract: Background: Diabetes care in our inner-city primary care clinic was suboptimal, despite provider education and performance feedback targeting improved adherence to evidence-based clinical guidelines. A crew resource management (CRM) intervention (communication and teamwork, process and workflow organisation, and standardised information debriefings) was implemented to improve diabetes care and patient outcomes. Objective: To assess the effect of the CRM intervention on adherence to evidence-based diabetes care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 17 publications
2
55
0
3
Order By: Relevance
“…19,[44][45][46] Although this scoping literature review is not focused on outcomes data, there appears to be a need for research that explores how the introduction of evidence-based practice influences patient care outcomes.…”
Section: Gaps: Implications For Researchmentioning
confidence: 97%
See 1 more Smart Citation
“…19,[44][45][46] Although this scoping literature review is not focused on outcomes data, there appears to be a need for research that explores how the introduction of evidence-based practice influences patient care outcomes.…”
Section: Gaps: Implications For Researchmentioning
confidence: 97%
“…It is important that leaders ensure that staff have the tools to carry out change, such as in the form of standardized documentation. 8,21,31,32,[42][43][44] In addition, there needs to be role clarity among staff members. That is, there needs to be a clear understanding of the responsibilities of different staff members, as blurred responsibilities may lead to the failure of an initiative.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Helitzer et al (2011) compared an interprofessional education programme to no intervention and reported significant gains in patient-centred communication skills. In controlled before-after studies, Ryskina et al (2009) reported more frequent assessment of haemoglobin A1c (HbA1c), cholesterol and blood pressure compared to usual single discipline care and Taylor et al (2007) similarly reported a significant increase in microalbumin and HbA1c testing. In other RCTs, Thompson et al found no significant difference in the detection of depression or detection of domestic violence cases when interprofessional education initiatives were compared to no intervention (Thompson et al, 2000a(Thompson et al, , 2000b.…”
Section: Introductionmentioning
confidence: 93%
“…These changes can lead to improved outcomes associated with chronic disease, such as diabetes, as demonstrated in several studies. [1][2][3] Barcelo group's A1C lowered from 8.4% to 7.9% (P < .01) compared to the usual care group's A1C lowering from 8.7% to 8.6% (P = .80). 1 Janson and colleagues 2 created an interprofessional team of primary care internal medicine residents, nurse practitioner students, and pharmacy students to improve the care of 384 patients with type 2 diabetes.…”
mentioning
confidence: 56%